دور المسؤولية الإجتماعية في تحقيق الميزة التنافسية لمنظمات الأعمال دراسة ميدانية لدى موظفي شركة إتصالات جازي بالجزائر. - حاقة, الأزهاري; حنيش, صلاح الدين; عبد ربي, بشير (جامعة الوادي - University of Eloued, 2022)
ف هذه الدراسة إلى التعرف على مدى تبني شركة الاتصالات الجزائرية جازي لمفهوم المسؤولية الاجتماعية على المجتمع الجزائري في بناء ميزتها التنافسية، والكشف عن أثر المسؤولية الاجتماعية على الميزة التنافسية. توصلت هذه الدراسة إلى أن مستوى توفر المسؤولية الاجتماعية بأبعادها والميزة التنافسية بأبعادها لدى موظفين كانت مرتفعة المستوى، كما تبين أن هناك تأثير علاقة ارتباط موجبة إحصائية ذات دلالة معنوية بين المسؤولية الاجتماعية والميزة التنافسية في المؤسسة محل الدراسة. This study aims to identify the extent to which the Djezzy telecom company in Algeria adopted the concept of social responsibility on the Algerian society in building its competitive advantage, and to reveal the impact of social responsibility on the competitive advantage. This study concluded that the level of availability of social responsibility in its dimensions and the competitive advantage in its dimensions among the employees of the company under study was high, and it was found that there is a positive statistically significant correlation between social responsibility and competitive advantage in the institution under study
The role of social responsibility in achieving the competitive advantage of business organizations, a field study among the employees of the Djezzy Telecom Company in Algeria
مقال
Keywords: المسؤولية الاجتماعية؛ الميزة التنافسية؛ الحصة السوقية؛ الصورة الذهنية.; Social responsibility; competitive advantage; market share; mental image